Pengaruh Kualitas Produk, Harga, dan Layanan terhadap Minat Berkunjung Kembali Konsumen Olympus Coffee di Kintamani, Bali - SITOMPUL, BELLA SILVIA; SURYAWARDANI, I GUSTI AYU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
The Influence of Product Quality, Price, and Service on Intention to Revisit Olympus Coffee Consumers in Kintamani, Bali.  The increasing competition for cafes in Kintamani is a challenge for Olympus Coffee. The purpose of this study was to analyze the effect of product quality, price, and service on consumer satisfaction and consumer intention to revisit Olympus Coffee. The research was conducted at Olympus Coffee in Kintamani, Bali. The type of data used is quantitative and qualitative data. The sample in this study was 75 respondents who visited Olympus Coffee at least once. The selection of respondents was carried out by purposive. Data analysis was carried out using the SEM method and analyzed using the Smart PLS Program. The results of this study indicate that: 1) The product quality of Olympus Coffee has a significant effect on customer satisfaction. This shows that increasing the quality of Olympus Coffee products will increase consumer satisfaction, 2) The price of Olympus Coffee products has a significant effect on consumer satisfaction. This shows that competitive prices will increase consumer satisfaction for Olympus Coffee, 3) The services provided by Olympus Coffee have a significant effect on customer satisfaction. This shows that the better the service provided by Olympus Coffee will increase customer satisfaction, 4) Olympus Coffee customer satisfaction has a significant effect on the intention to return. This shows that increasing customer satisfaction will increase the interest to visit again. Suggestions for Olympus Coffee, it is expected to improve the quality of products and services and adjust prices to increase competitiveness.